2019
DOI: 10.1111/jre.12724
|View full text |Cite
|
Sign up to set email alerts
|

Validation of self‐reported measures of periodontitis in a Spanish Population

Abstract: Background and Objective: Use of self-reported questionnaires in Dentistry may be useful to estimate the prevalence of periodontitis in epidemiological studies. This study aims to assess the accuracy of self-reporting for predicting the prevalence of periodontitis in a Spanish population participating in a diabetes incidence study. Materials and Methods: Data were collected from 231 patients participating in the Di@bet.es study. Eight questions about periodontal health were included in a health patient-reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 37 publications
6
45
0
2
Order By: Relevance
“…Concerning the outcome, i.e., periodontitis, this was assessed by calculating a probability score (mPESS) that was recently developed on the basis of self-report questions for the screening and surveillance of periodontitis, already used and validated in several countries. [26][27][28][29][30] However, this remains a self-report measure of the individual probability of suffering from severe periodontitis that cannot be directly translated into a clinical diagnosis. The association between the exposure (alcoholic beverage consumption) and the outcome (self-reported severe periodontitis) was evaluated by taking into account multiple confounders, including several socio-demographic variables that may influence this association.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the outcome, i.e., periodontitis, this was assessed by calculating a probability score (mPESS) that was recently developed on the basis of self-report questions for the screening and surveillance of periodontitis, already used and validated in several countries. [26][27][28][29][30] However, this remains a self-report measure of the individual probability of suffering from severe periodontitis that cannot be directly translated into a clinical diagnosis. The association between the exposure (alcoholic beverage consumption) and the outcome (self-reported severe periodontitis) was evaluated by taking into account multiple confounders, including several socio-demographic variables that may influence this association.…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis was explored by using questions originally proposed in the questionnaire of the Centers for Disease Control and Prevention and the American Academy of Periodontology (CDC/AAP), 26 that has been widely used in several countries for the screening and surveillance of periodontal diseases. [27][28][29] These questions have also been translated into French by using the standardized method of backward translation, tested and re-tested for comprehension, and then validated against a full-mouth clinical periodontal examination to assess their diagnostic accuracy (see Table S1 in online Journal of Periodontology). 30 Moreover, Carra et al developed a user-friendly score to estimate the individual probability to suffer from severe periodontitis, namely the Periodontal Screening Score (PESS), based upon five selected self-report items, including the evaluation of gum and teeth health (categorized into three classes: excellent-to-good, fair, and poor), the treatments received for gum disease (yes/no), the presence of loose tooth (yes/no), the report of having lost bone around teeth (yes/no), and the perception that a tooth does not look right (yes/no).…”
Section: Oral Health and Periodontitis Assessmentmentioning
confidence: 99%
“…Previous studies [18,[24][25][26][27][28] in the USA, Spain, France, and Germany were performed in a similar way as the study from Verhulst et al [1]. They all used only SROH questions and demographic data to predict severe periodontitis; no oral examination was needed to predict the periodontal state.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have shown little progress in using individual or joint perceived measures to identify individuals with periodontal disease 36,37 . Alternative items to those used in National Health and Nutrition Examination Survey (NHANES) (and thus in this study) have been proposed such as gum bleeding, teeth getting longer, halitosis, use of interdental devices, and food impaction 38‐40 . It is still uncertain whether these items could improve the PPM and will need to be further evaluated.…”
Section: Discussionmentioning
confidence: 99%